A heat-inactivated H7N3 vaccine induces cross-reactive cellular immunity in HLA-A2.1 transgenic mice. Issue 1 (December 2016) - Di Mario, Giuseppina; Garulli, Bruno; Sciaraffia, Ester; Facchini, Marzia; Donatelli, Isabella; Castrucci, Maria
Abstract Background Cross-reactive immunity against heterologous strains of influenza virus has the potential to provide partial protection in individuals that lack the proper neutralizing antibodies. In particular, the boosting of memory CD8+ T cell responses to conserved viral proteins can attenuate disease severity caused by influenza virus antigenic variants or pandemic strains. However, little is yet known about which of these conserved internal antigens would better induce and/or recall memory CD8+ T cells after in vivo administration of an inactivated whole virus vaccine. Methods We explored the CD8 + T cell responses to selected epitopes of the internal proteins of an H7N3 influenza virus that were cross-reactive with A/PR/8/34 virus in HLA-A2.1 transgenic (AAD) mice. Results CD8+ T cells against dominant and subdominant epitopes were detected upon infection of mice with live H7N3 virus, whereas immunization with non-replicating virus elicited CD8+ T cell responses against mostly immunodominant epitopes, which were rapidly recalled following infection with A/PR/8/34 virus. These vaccine-induced T cell responses were able to reduce the lung viral load in mice challenged intranasally with the heterologous influenza virus. Conclusions A single immunization with non-replicating influenza virus vaccines may be able to elicit or recall cross-reactive CD8+ T cell responses to conserved immunodominant epitopes and, to some extent, counteract an infection by heterologous virus.